INTEGRATION OF SOUTHEAST ASIAN STOCK MARKETS WITH THE WORLD STOCK MARKET: APPLICATION OF INTERNATIONAL ASSET PRICING MODEL - Maksar, Muhammad Sofian; Setiawan, Kusdhianto; Adnan Hakim, Al Asy Ari (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2022)
This study aims to determine the integration level of Southeast Asian stock market with the world stock market using an international capital asset pricing model. The countries that were sampled in this study were Indonesia, Malaysia, Philippines, Singapore and Thailand. The sample period starts from January 2000 until August 2016. This study uses an partially-segmented international capital asset pricing model by including the assumption of residual that were correlated between asset pricing equations. Because of this assumption, the seemingly unrelated regression (SUR) estimation method is more appropriately compared to the ordinary least square (OLS) method. The results of this study indicate that the integration level of Southeast Asian stock market varies. The Singapore and Thailand stock markets are fully integrated with the world stock market, the Indonesian and Malaysian stock markets are partially integrated with the world stock market, while the Philippine stock market is segmented with the world stock market. This finding shows the difference in the effectiveness of the stock market liberalization process in Southeast Asia